Trasplante simultáneo de riñón y páncreas en pacientes con diabetes mellitus de tipo 1, Clínica Fundación Valle del Lili, Cali, 2001-2013 (2014)
Clinical outcomes in patients with Type 1 diabetes mellitus (DM 1) after simultaneous kidney-pancreas transplantation (SRP) and end stage renal disease have shown to be a therapeutic option with successful clinical results, making it the best metabolic control option for this population group. Objective. Clinical results show the short and medium term DM1 patients undergoing simultaneous kidney transplantation - Pancreas (SRP) in our institution. Material and method. Institutional registry of renal transplantation (Trenal), which includes 1300 patients, we selected patients undergoing simultaneous kidney pancreas transplantation. We performed a nonparametric statistical analysis and survival was estimated by Kaplan-Meier. Results. Between 2001 and 2012 there were a total of 27 simultaneous kidney - pancreas transplants , individuals mostly male (59%), with age at transplant of 34, a time from the diagnosis of DM I 22 years. The goal of achieving glycemic control was achieved in 24 to 48 hours post-op. The patient survival rate at one and two years is 92% and 87%, and of the pancreatic graft at one year was 88%, values comparable to the best expected results. Conclusion. The simultaneous kidney-pancreas transplantation is a therapeutic option with good clinical results in patients with DM1 and end stage renal disease. The small number of the sample reflects not only the difficulties in obtaining donors, but also the lack of diffusion and recognition of potential candidates, hence the importance of the diffusion of existing experience in order to facilitate access to the best treatment option.